(untitled) (UNED Research Journal, 2020)
Introduction: The corals reef of Golfo Dulce, South Pacific, Costa Rica, are disappearing due to anthropogenic pollution and sedimentation. Objective: To develop a coral nursery, and establish its viability to subsequently perform a restoration of scleractinian corals in the Pacific of Costa Rica, between December 2014 and May 2016. Methods: We placed the coral nursery structure in the middle of the water column in the Punta Encanto sector, Golfo Dulce using some fragments of coral collected from Porites lobata, Psammocora stellata and Pavona varians, placed in cement “cookies” to make a monthly three-dimensional measurement of growth, and taking water samples for physicochemical analyses. Results: We found that the species Psammocora stellata gave better results in the nursery and that the lowest concentration of nutrients was in the middle of the water column, where silicates were the most abundant throughout the period of the study. In general, we can say that the levels of nutrients are normal in comparison to other studies, however; the phosphate concentration adversely affected all the species in terms of growth, as well as the high salinity. Conclusion: coral gardening is feasable in the Golfo Dulce as a technique for ecological restoration.